Living the farm sanctuary life : the ultimate guide to eating mindfully, living longer, and feeling better everyday - Baur, Gene; Stone, Gene, 1951- (Rodale, 2015)
Gene Baur, the cofounder and president of Farm Sanctuary, the nation's leading farm animal protection organization, knows that the key to happiness lies in aligning your beliefs with your actions. In this definitive vegan and animal-friendly lifestyle guide, he and Gene Stone, author of Forks Over Knives, explore the deeply transformative experience of visiting the sanctuary and its profound effects on people's lives. The book covers the basic tenets of Farm Sanctuary life--such as eating in harmony with your values, connecting with nature wherever you are, and reducing stress--and offers readers simple ways to incorporate these principles into their lives.